Formation of a System for Detection and Recognition of the Unmanned Aerial Vehicles - Babich, A. P.; Kibitkin, S. O.; Georgiev, Yu. V.; Belzetskyi, R. S. (Visnyk of Vinnytsia Politechnical Institute, 2024)
The problematic issues of combating unmanned aerial vehicles (UAVs) are investigated. It is determined that due to the cheapness and large-scale production capabilities, the enemy has begun to actively use UAVs such as kamikaze strike drones and drones with drops (bombers), in particular FPV-drones. It is proved that the level of threat of such UAVs — battlefield drones is determined not only by their ability to select priority targets, and build an optimal trajectory even at the stage of attacking the target, but also by the difficulty of counteracting such means of destruction. For the most part, the problem of countering drones is related to the difficulty of their timely detection. Without solving this problem, the most modern means of fire destruction are unable to reliably counteract such a threat. It is proposed that, along with the classical detection methods, namely: acoustic, optical, radio engineering, radar, to use such detection methods as aerial and agent reconnaissance. The essence of this method is to determine the launch sites of drones, which allows to destroy enemy UAVs with mortar and small arms fire before the use of drones or to warn and target the detection system regarding the possible direction of use of drones and even their types. The basic principles of the formation of a detection and recognition system are defined and substantiated, which will allow to take into account the characteristics of drones as air targets, timely detect them and provide information to fire and electronic warfare. As the experience of the Russian-Ukrainian war shows, a system for detecting and recognizing air threats to troops and objects on the battlefield should be formed on the following principles: a combination of means in which detection methods are implemented and organizational measures for the use of these means; the ability to monitor and analyze the state and trends of the battlefield, planning options for using the system in accordance with the current or projected situation; constant collection of information on the movement of enemy UAVs, places of deployment.